Polyserine domains are toxic and exacerbate tau pathology in mice - Meaghan Van Alstyne; Vanessa L. Nguyen; Charles A. Hoeffer; Roy Parker (Proceedings of the National Academy of Sciences, 2026)
Polyserine domains mediate the association of some nuclear RNA-binding proteins with cytoplasmic tau aggregates occurring in tauopathy models and patient samples. In cell lines, polyserine domains mediate colocalization with tau aggregates and promote formation, suggesting that the cytoplasmic mislocalization of polyserine-containing proteins could contribute to human disease. Moreover, polyserine can be produced by repeat-associated non-AUG translation in CAG repeat expansion diseases. However, whether polyserine expressed in a mammalian brain is toxic and/or can exacerbate tau pathology is unknown. We used AAV9-mediated delivery to express a 42-repeat polyserine protein in wild-type and tau transgenic mouse models. We observe that polyserine expression has toxic effects in wild-type animals indicated by reduced weight, behavioral abnormalities, and a striking loss of Purkinje cells. Moreover, in the presence of a pathogenic variant of human tau, polyserine exacerbates disease markers such as phosphorylated and insoluble tau levels and the seeding capacity of brain extracts. These findings demonstrate that polyserine domains can promote tau-mediated pathology in a mouse model and support the hypothesis that polyserine-containing proteins could contribute to the progression of human tauopathies.